THE GENE OF HAPPINESS AND ITS IMPACT ON STUDENTS’ ACADEMIC PERFORMANCE - Akishev Karshyga; Akisheva Lenara (Foundations and Trends in Modern Learning, 2023)
The post-pandemic period revealed a process of declining student performance and loss of interest in learning. This process tends to grow regardless of the course and form of study of students in many countries . Today, due to globalization, the deterioration of the ecological situation on the planet, economic and political problems, there is a relationship between the so-called "happiness" gene and the behavioral mood of an individual. Conducted in various countries, scientific studies have discovered a gene that has received the abbreviation 5-HTTLPR and whose role is to determine the amount of the hormone serotonin in the human brain. Serotonin is a hormone that affects a person’s mood. There are medications that provide an increase in the level of serotonin in the body. To date, 3 types of genes have been identified. 2 affect the risk of depression and the possibility of suicide of an individual. One affects the stability in the event of stressful situations [1]. In particular, British scientists conducted studies of several thousand, observing the 5-HTTLPR gene, it was noticed that individuals with 2 copies of this gene, as a rule, are programmed for good luck in life, as well as the absence of a change in mood. Individuals with low serotonin content are more prone to depression, they have anxiety symptoms, lack of motivation, faith in the future [2]. It is noteworthy that the organizer, the research Zh. de Neve conducted a survey of more than 2.5 thousand respondents who were asked about life satisfaction, as a result of data analysis, it was revealed that 19% are not satisfied with life [3-4].